2001
DOI: 10.1046/j.1439-0442.2001.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nandrolone Treatment on Recovery in Horses After Strenuous Physical Exercise

Abstract: To test the effect of nandrolone on their recovery, six adult half-bred riding horses performed a competition exercise test (CET) and a standardized exercise test (SET) on consecutive days before and after a 2-week treatment with the anabolic steroid nandrolone laurate. Blood samples were collected during and between these tests for the determination of red cell volume and concentrations of blood lactate, plasma glucose, non-esterified fatty acids, glycerol, triglycrides, erythropoietin, cortisol, insulin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…On the other hand, another study failed to detect an increase in red cell volume or erythropoietin levels (Hyyppä 2001). This was attributed to a shorter duration of treatment with nandrolone laurate in this study than the previous studies.…”
Section: Anabolic Steroids and Red Blood Cellscontrasting
confidence: 80%
See 2 more Smart Citations
“…On the other hand, another study failed to detect an increase in red cell volume or erythropoietin levels (Hyyppä 2001). This was attributed to a shorter duration of treatment with nandrolone laurate in this study than the previous studies.…”
Section: Anabolic Steroids and Red Blood Cellscontrasting
confidence: 80%
“…Several studies have examined the effect of anabolic steroids on various muscle characteristics. Muscle water content does not appear to be changed by treatment (Nimmo et al 1982;Snow et al 1982a) nor does muscle glycogen content (Nimmo et al 1982;Snow et al 1982a;Hyyppä et al 1997;Hyyppä 2001), nor total mean protein concentration (Nimmo et al 1982;Snow et al 1982a;Hyyppä et al 1997). Total mean protein concentration did, however, increase during the follow-up period after treatment (Hyyppä et al 1997).…”
Section: Anabolic Steroids and Musclementioning
confidence: 88%
See 1 more Smart Citation
“…Published data in horses with clinical disease related to muscle recovery are limited. Nandrolone increased the rate of muscle glycogen repletion in treated animals after strenuous exercise (Hyyppa 2001). Whether strenuous exercise correlates well with muscle damage during clinical disease is unclear.…”
Section: Anabolic Steroids and Muscle Recovery And Cachexia/debilitationmentioning
confidence: 99%
“…In contrast to the well‐documented advantages that anabolic steroids offer to human athletes, the effects of anabolic steroids in equine competitors are not well‐established . A study has shown that short‐term nandrolone (17β‐hydroxyestr‐4‐en‐3‐one) administration increased the glycogen content of post‐exercise muscle tissue; however, this is in contrast with two studies that found no observable changes resulting from nandrolone administration . It has been shown that steroid administration delayed closure of epiphyseal growth plates in Standardbreds, and suggested that this could lead to a potential increase to the long‐term risks of injury during training .…”
Section: Anabolic Steroids In Equine Sportsmentioning
confidence: 99%